Sea-ice-related halogen enrichment at Law Dome, coastal East Antarctica - Vallelonga P.; Maffezzoli N.; Moy A. D.; Curran M. A. J.; Vance T. R.; Edwards R.; Hughes G.; Barker E.; Spreen G.; Saiz-Lopez A.; Corella J. P.; Cuevas C. A.; et al. (Climate of the Past, 2017)
The Law Dome site is ideal for the evaluation of sea ice proxies due to its location near to the Antarctic coast, regular and high accumulation throughout the year, an absence of surface melting or remobilization, and minimal multiyear sea ice. We present records of bromine and iodine concentrations and their enrichment beyond seawater compositions and compare these to satellite observations of first-year sea ice area in the 90-130°ĝ€E sector of the Wilkes coast. Our findings support the results of previous studies of sea ice variability from Law Dome, indicating that Wilkes coast sea ice area is currently at its lowest level since the start of the 20th century. From the Law Dome DSS1213 firn core, 26 years of monthly deposition data indicate that the period of peak bromine enrichment is during austral spring-summer, from November to February. Results from a traverse along the lee (western) side of Law Dome show low levels of sodium and bromine deposition, with the greatest fluxes in the vicinity of the Law Dome summit. Finally, multidecadal variability in iodine enrichment appears well correlated to bromine enrichment, suggesting a common source of variability that may be related to the Interdecadal Pacific Oscillation (IPO).